Classically intoxicated: correlations between quantity of alcohol consumed and alcohol related problems in a classical Greek text. Issue 7633 (20th December 2007) - Cook, Christopher C H; Tarbet, Helen; Ball, David
Abstract : From fragments of a play, Christopher Cook, Helen Tarbet, and David Ball discover that you couldn't teach the ancient Greeks much about drunkenness